Endoscopic Surgical Repair of a Giant, Postoperative, Neglected Meningoencephalocele - Kosmidou, Panagiota (Cureus, 2020)
Meningoencephalocele is a rare and potentially lethal disease, requiring early diagnosis and treatment. A 30-year-old male patient was diagnosed with a massive meningoencephalocele. His medical history included cerebrospinal fluid (CSF) rhinorrhea since the age of 7 years, which was attributed to right eye mining during infancy due to Coats disease. Following failed attempts of open surgical repair and CSF diversion during childhood, no further attempts of surgical management were made. He presented a long history of recurrent episodes of meningitis, resulting in long-lasting hospitalization in the intensive care unit. Eventually, he underwent surgical repair through an endoscopic multilayer approach. Subsequent endoscopic and radiological assessment demonstrated no recurrence during a follow-up period of one year. Endoscopic treatment is highly successful. An effective and definite surgical repair is of paramount importance in order to avoid life-threatening complications, improve patient’s and caregiver’s quality of life, and avoid unnecessary health-system costs.